2020
DOI: 10.1002/art.41253
|View full text |Cite
|
Sign up to set email alerts
|

Early Disease and Low Baseline Damage as Predictors of Response to Belimumab in Patients With Systemic Lupus Erythematosus in a Real‐Life Setting

Abstract: Objective. To investigate predictors of response, remission, low disease activity, damage, and drug discontinuation in patients with systemic lupus erythematosus (SLE) who were treated with belimumab.Methods. In this retrospective study of a multicenter cohort of SLE patients who received intravenous belimumab, the proportion of patients who achieved remission, low disease activity, and treatment response according to the SLE Responder Index 4 (SRI-4) was determined, and the Systemic Lupus International Collab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
75
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 33 publications
19
75
4
2
Order By: Relevance
“…Since additional treatment is not always needed in patients with cSLEDAI=0 despite PGA ≥0.5, and since these items showed overlapping sensitivity, specificity, positive and negative predictive value against damage accrual (table 6 and figure 2), adding PGA <0.5 to cSLEDAI=0 could lead to overtreatment in controlled trials as well as in clinical practice when a treatto-target (T2T) approach is adopted. 21 In fact, T2T should aim at the most reachable target that positively influences patient prognosis. We observed that cSLEDAI=0 was the definition of remission easiest to achieve in real life, being able to predict damage accrual with a consistent degree of accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since additional treatment is not always needed in patients with cSLEDAI=0 despite PGA ≥0.5, and since these items showed overlapping sensitivity, specificity, positive and negative predictive value against damage accrual (table 6 and figure 2), adding PGA <0.5 to cSLEDAI=0 could lead to overtreatment in controlled trials as well as in clinical practice when a treatto-target (T2T) approach is adopted. 21 In fact, T2T should aim at the most reachable target that positively influences patient prognosis. We observed that cSLEDAI=0 was the definition of remission easiest to achieve in real life, being able to predict damage accrual with a consistent degree of accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a simplified remission definition based on cSLEDAI=0 can be reasonably used in observational studies where complete serological data, PGA and BILAG are not routinely assessed. 21 In the cSLEDAI=0 remission definition, the exclusion of a cut-off for PDN could imply that high dose glucocorticoids may mask disease activity, thus allowing patients not in real remission to be defined as remitted. Nevertheless, we found that adding PDN ≤5 mg/day to cSLEDAI=0 does not increase the performance against damage of cSLEDAI=0 in the short/medium term (5 years), as shown by the high overlap between confidence intervals.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…"It has been shown that belimumab may be more protective of long-term organ damage in patients with SLE with longer periods of remission or low disease activity." 6 This exploratory analysis suggested that belimumab plus standard therapy may slow the rate and magnitude of organ damage accrual compared with standard therapy alone. This analysis of a larger and more diverse US and non-US pooled population was consistent with our previously published US-focused study.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, biologics can help attain remission and LDA and, in turn, dampen damage progression. 9 Learning Objectives . Discuss the major targets in SLE management and their timing in a sequential strategy .…”
Section: Learningmentioning
confidence: 99%